1996
DOI: 10.1159/000177142
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Sudden Cardiac Death for Patients with Chagas’ Disease: A Hospital-Derived Cohort Study

Abstract: This study was carried out to identify patients with Chagas’ disease at risk of sudden cardiac death, inasmuch as such patients have not been recognized thus far. Seventy-four consecutive patients with a positive complement fixation test for Chagas’ disease prospectively followed up at the Cardiomyopathy Clinic from January 1990 to June 1993 were entered into the study. Patients underwent medical history, physical examination, serological tests, resting electrocardiography, chest X-ray and two-dimensional echo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 20 publications
(31 reference statements)
2
60
0
2
Order By: Relevance
“…Two articles from an external source were added to this overview: a manuscript that had just been accepted for publication in a peer-reviewed journal 23 and a relevant study (published as an abstract) 24 that was identified by searching for bibliographies in all retrieved articles. Thus, 12 studies [21][22][23][24][25][26][27][28][29][30][31][32] satisfied the prespecified inclusion and exclusion criteria and constitute the basis of this investigation. Table 1 summarizes the characteristics of the 12 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles from an external source were added to this overview: a manuscript that had just been accepted for publication in a peer-reviewed journal 23 and a relevant study (published as an abstract) 24 that was identified by searching for bibliographies in all retrieved articles. Thus, 12 studies [21][22][23][24][25][26][27][28][29][30][31][32] satisfied the prespecified inclusion and exclusion criteria and constitute the basis of this investigation. Table 1 summarizes the characteristics of the 12 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the 12 studies. Year of publication [21][22][23][24][25][26][27][28][29][30][31][32] ranged from 1991 to 2006. Investigators enrolled subjects over several years, and the most studies referred to Brazilian cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of sudden death is obviously not the same for every chagasic patient; therefore, several authors 25,27,29,[30][31][32]50,[59][60][61][62][63][64][65][66][67][68][69][70][71][72] have tried to identify factors predisposing certain patients to a higher risk of this catastrophic event. Therefore, variables, such as presyncope and syncope, ventricular dysfunction and heart failure, complex nonsustained and sustained ventricular arrhythmias, severe bradyarrhythmias (sinus node dysfunction and advanced atrioventricular blocks), and previous cardiac arrest have been identified as predictors of the risk of sudden death, at least in some studies.…”
Section: Identification Of Groups At Riskmentioning
confidence: 99%
“…The systemic infection is generally acquired at an early age (6,7) by vector transmission, although an acute form of parasitic transmission has been increasingly reported in affected countries (8), and may represent a noteworthy healthcare-related problem in Europe and the United States due to migration (9). Its insidious and asymptomatic course, ranging from 10 to 30 years, and eventual advance to myocardial dysfunction, occurring in up to 30% of infected subjects, represents a marker of unfavorable prognosis for cardiovascular morbidity and mortality (10)(11)(12)(13). In this setting, persistent or permanent AF has been observed in up to one fifth of subjects bearing the chronic form (14) and represents a superimposed sign of poor prognosis (7,8).…”
Section: Introductionmentioning
confidence: 99%